Vaccinia virus: it's use in smallpox vaccine and epidemiology - Megid, Jane [UNESP] (My University, 2014)
Vaccinia Virus (VACV) was widely used in smallpox vaccines in Brazil during the world vaccination campaign of Word Health Organization. After ends of this campaign in Brazil in 1980, zoonotic Vaccinia outbreaks have been recorded in several regions of the country. Researches believed that the VACV used in the word vaccination campaign in Brazil was involved in the re-emergence of the disease. To analyze the similarity between the viruses isolated from outbreaks and those used during Smallpox eradication, phylogenetic analyzes of vaccines viruses were compared to VACV isolated in outbreaks, and the result obtained was that Brazilians VACV are not grouped with vaccines viruses. The origin of outbreaks remains unknown in Brazil, but the most accepted theory assumes that there is populations of VACV genetically diverse circulating in still unknown natural reservoirs, and according on biological and geographical conditions are transmitted to cows and human beings. There is little information about natural reservoirs of VACV. It is believed that some species of Rodent Order act as VACV natural reservoirs. Although, studies have demonstrated the possible of transmission of VACV from mice experimentally infected to cow, this interaction has not yet been proven in natural environment. There are two genetically distinct groups of VACV circulating in Brazil. Experimentally these two groups also differ biologically, but no difference in clinical signs was observed during outbreaks. This review analyzed VACV natural history and epidemiological studies conducted in the last years in Brazil.
Keywords: Orthopoxvirus; Smallpox virus; Vaccinia virus; Epidemiology; Natural history; Origins